Effects of hemp-based polyunsaturated fatty acid supplementation on membrane lipid profiles and reproductive performance in Martina Franca jacks - Fusaro, Isa; Parrillo, Salvatore; Buonaiuto, Giovanni; Prasinou, Paraskevi; Gramenzi, Alessandro; Bucci, Roberta; Cavallini, Damiano; Carosi, Alessia; Carluccio, Augusto; De Amicis, Ippolito (Frontiers in Veterinary Science, 2025)
This study evaluates the impact of dietary supplementation with hemp-based polyunsaturated fatty acids (PUFAs) on the membrane lipid profiles and reproductive performance of Martina Franca jacks. Over a 90-day period, twelve donkeys were divided into a treatment group receiving hemp oil and a control group on a standard diet. Semen and blood samples were collected and analyzed at multiple time points for lipid composition and reproductive parameters. Results revealed that sperm motility improved significantly, increasing from 92.61% in the control group to 96.63% by Day 60 in the treatment group (p = 0.05). Normal sperm morphology also showed a significant enhancement, rising from 96.58% in the control group to 98.85% by Day 60 (p = 0.04). Conversely, gel-free semen volume decreased significantly in the treatment group, from 64.17 mL in the control group to 28.20 mL at Day 60 (p < 0.0001). Lipidomic analyses indicated an increased proportion of omega-3 PUFAs, such as eicosapentaenoic acid (EPA; 0.08% in the control group to 0.20% by Day 60, p < 0.0001), in sperm membranes, alongside a reduction in the peroxidation index (264.11 in the control group to 86.53 in the treatment group, p < 0.0001). These changes suggest improved membrane fluidity and oxidative stability. These findings underscore the potential of hemp oil as a dietary supplement to enhance reproductive outcomes in donkeys, with broader implications for livestock management.